2022
DOI: 10.3390/nu14040755
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 12-Week Intake of Nicotinamide Mononucleotide on Sleep Quality, Fatigue, and Physical Performance in Older Japanese Adults: A Randomized, Double-Blind Placebo-Controlled Study

Abstract: Deteriorating sleep quality and physical or mental fatigue in older adults leads to decreased quality of life and increased mortality rates. This study investigated the effects of the time-dependent intake of nicotinamide mononucleotide (NMN) on sleep quality, fatigue, and physical performance in older adults. This randomized, double-blind placebo-controlled study evaluated 108 participants divided into four groups (NMN_AM; antemeridian, NMN_PM; post meridian, Placebo_AM, Placebo_PM). NMN (250 mg) or placebo w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 35 publications
(49 reference statements)
3
35
0
Order By: Relevance
“…Clinical benefits of NMN supplementation in mouse models have shown doubled running endurance on aging mice [ 6 ], restored cognition in Alzheimer’s disease rat model [ 7 ], and reversed vascular dysfunction in old mice [ 8 ]. However, human clinical trials with NMN are limited [ 9 17 ]. The first human clinical trial confirmed that NMN supplementation was safe up to 500 mg/day and plasma concentrations of NAD metabolites were significantly increased, but the changes of plasma NAD concentration were not mentioned, and the trial was an open-label single oral dosing with only 10 healthy male participants [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical benefits of NMN supplementation in mouse models have shown doubled running endurance on aging mice [ 6 ], restored cognition in Alzheimer’s disease rat model [ 7 ], and reversed vascular dysfunction in old mice [ 8 ]. However, human clinical trials with NMN are limited [ 9 17 ]. The first human clinical trial confirmed that NMN supplementation was safe up to 500 mg/day and plasma concentrations of NAD metabolites were significantly increased, but the changes of plasma NAD concentration were not mentioned, and the trial was an open-label single oral dosing with only 10 healthy male participants [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A 6-week RCT with healthy amateur athletes with 300, 600, and 1200 mg/day NMN oral regimens concluded that exercise plus NMN supplementation was significantly and dose-dependently increased aerobic capacity but found no impact on physical strength when compared to exercise alone [ 16 ]. Another RCT on the effects of the time-dependent intake (morning or afternoon) of NMN on sleep quality, fatigue, and physical performance in older adults was conducted with 250 mg/day NMN oral treatment for 12 weeks [ 17 ]. The trial found that only drowsiness and lower limb function in the afternoon NMN-treated group were significantly improved among the many trial end points measured.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 250 mg of daily NMN supplementation was shown to be well tolerated, efficacious when increasing NAD+/NADH ratio, and improved muscle function in aged but otherwise healthy men [68]. NMN supplementation has also been implicated in improving circadian paraments in older adults, where 12 weeks of 250mg daily NMN supplementation led to improvements in sleep quality, as measured through the PSQI, fatigue, and physical performance [69]. Having established the safety and efficacy of NMN supplementation to increase NAD+ levels in the body, numerous trials analyzing the effects of NMN on health, aging, and disease are constantly emerging.…”
Section: Nmn As An Nad+ Boosting Therapeuticmentioning
confidence: 99%
“…To date, published studies of NR have mostly evaluated its bioavailability [ 33 ], whereas there have been some recent studies of NMN that have evaluated clinical outcomes in older adults. A 12-week period of treatment with NMN reduced drowsiness and improved leg function in older people [ 34 ]. A randomised clinical trial in 25 obese postmenopausal women found that 10 weeks of NMN compared to placebo was associated with improved insulin sensitivity in muscle but not liver or adipose tissue [ 35 ].…”
Section: Nutrient Sensing Pathwaysmentioning
confidence: 99%